Huevo, larva en primer estadio y aparato genital femenino de la mariposa Chabuata castanea (Lepidoptera: Noctuidae) - A. Rodríguez, Marcela (2007)
Egg, first larval stage, and female genitalia of the widely distributed moth Chabuata castanea are described, based on material from Talcahuano, VIII region, Chile. Egg microestructures are illustrated with scan-nig electron microscope images which show that egg morphology allows identification to species level.